2016
DOI: 10.1093/cid/ciw629
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and Valuing Community Health Worker Time in Improving Access to Malaria Diagnosis and Treatment

Abstract: Background. Community health workers (CHWs) are members of a community who are chosen by their communities as first-line, volunteer health workers. The time they spend providing healthcare and the value of this time are often not evaluated. Our aim was to quantify the time CHWs spent on providing healthcare before and during the implementation of an integrated program of diagnosis and treatment of febrile illness in 3 African countries.Methods. In Burkina Faso, Nigeria, and Uganda, CHWs were trained to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…When given an opportunity to report challenges, the time taken to do COSMIC related activities was not mentioned. Our ndings echo other studies that found CHWs increasingly involved in CSST programmes face signi cant challenges [24,38]. The results vary depending on the setting.…”
Section: Discussionsupporting
confidence: 84%
“…When given an opportunity to report challenges, the time taken to do COSMIC related activities was not mentioned. Our ndings echo other studies that found CHWs increasingly involved in CSST programmes face signi cant challenges [24,38]. The results vary depending on the setting.…”
Section: Discussionsupporting
confidence: 84%
“…Severe malaria reflects delays in effective antimalarial treatment. Speed of recovery is important for the child and the family who bear the costs [12]. Reassuringly, there were very few severe malaria cases, even fewer malaria-negative patients treated with an ACT, and deaths were rare.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the intervention was evaluated through pre- and post-quantitative household surveys to assess impact (changes in treatment-seeking behavior), qualitative surveys that documented acceptability of the program [11], and an economic evaluation of the package [12]. In addition, CHW performance was assessed.…”
Section: Methodsmentioning
confidence: 99%
“…CHWs provided voluntary services to underserved populations but were evaluated and held accountable as if they were salaried workers and were aggrieved to learn that community members did not understand or appreciate the volunteer nature of their contribution. Although the time they spent on healthcare was small [16], the cost savings to the community were significant [9] in a context where formal health services were limited. The existing evidence overwhelmingly suggests that CHWs are a good investment in providing access to and coverage of basic health services.…”
Section: Discussionmentioning
confidence: 99%